Investigation into Morphology of Cavitation Erosion-Corrosion Pits on the Surface of Carbon Steel (The International Journal of Engineering & Information Technology (IJEIT), 2014)
Nano-sized films associated with the ring areasformed around micropits in cavitation erosion experimentswere investigated. The corrosion behavior and vibratory cavitation erosion tests of mild carbon steel in 3% NaCldistilled water were carried out. The results showed that thenano-sized films associated with the ring areas formedaround micropits in cavitation and free cavitation tests havea similar shape. The study proved that the nano-structure and the ring areas formed around micropits are the result ofcorrosion effects and not as a result of thermal effectsrelated to the collapse of the bubbles.